Optimalisasi Peran Kader PKK dalam Pengelolaan Obat Rumah Tangga Melalui Edukasi DAGUSIBU dengan metode CBIA - Yeni Farida; Rini Budi Astuti; Rasmaya Niruri; Vinci Mizranita; Novita Dhewi Ikakusumawati; Tiara Dewi Salindri Pratama; Inayatush Sholihah (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Limited access to healthcare services in Karangturi Village is one of the factors contributing to the practice of self-medication. Without adequate knowledge, self-medication may increase the risk of medication errors. Therefore, improving public understanding of DAGUSIBU (Obtain, Use, Store, and Dispose of Medicines Properly) is essential. This community service program aimed to enhance knowledge of DAGUSIBU through the empowerment of Family Welfare Movement (PKK) using the Community-Based Interactive Approach (CBIA) educational method. The program was conducted in three stages: preparation of permits and educational materials, implementation of the educational intervention, and evaluation through a written post-test and oral feedback. Among the 44 participants, post-test results showed a 100% correct response rate on questions related to information to consider when purchasing medicines, medication administration instructions, storage, management of missed doses, handling of adverse effects, and medicine disposal. The lowest percentage of correct responses was observed for questions regarding the identification of adverse drug effects. Overall, the findings indicate that the educational intervention successfully improved participants’ knowledge of DAGUSIBU. It is expected that the trained PKK cadres will disseminate the acquired knowledge to other PKK members, thereby promoting appropriate household medication management practices within the community.